An Analysis of the Students’ Writing Skill in Hortatory Exposition Text at the First Semester of Public Administration Study Program of the Faculty of Social and Political Science - Amanda Pradhani Yanwar (UIR Press, 2020)
This research aimed to describe the students’ difficulties in writing Hortatory Exposition Text and describe the students’ scores in writing Hortatory Exposition Text. The research was descriptive qualitative research. It was conducted at the first semester of Public Administration Study Program of the faculty of Social and Political Science Universitas B. The population of this research was 40 students of the first semester of Public Administration Study Program of the Faculty of Social and Political Science Universitas B. Simple random sampling was applied to select the sample. The researcher took 3 participants consisting of one low, one medium, and one high student based on English language proficiency level. In collecting the data, the researcher used test, observation, and interview. In analyzing the data, the researcher used a flow model. The result of the research showed that the low-level student (PE) got the lowest score, and the high-level student (JN) got the highest score. In addition, the aspects of writing the students had the most difficulties in were organization, unity, coherence, sentences, and paragraphs.